(untitled) (ELang | An English Language Education Journal, 2020)
The research study entitled “The correlation between students listening ability and speaking skill”. This correlation study done in the first semester of regular of English Education Study Program at Bale Bandung University 2019/2020 academic year consisted of 27 students. The research questions of this research (1) Is there any correlation between students’ listening ability and their speaking skill? (2) If there is correlation it is high, moderate, and low? To answer the research, the researcher used Pearson Product Moment. It was found that the derived t = 5.071 is greater the table critical value of t = 2.060, at p = .05 with df = 25 (5.071>2.060). It was proved by the result of the analysis that the r value is 0.213. The result of this research showed that there correlation between students’ listening ability and their speaking skill. And the correlation is low between students listening and speaking skill.